THE EFFECTIVENESS OF QUIZIZZ IN ENHANCING JUNIOR HIGH SCHOOL STUDENTS' READING COMPREHENSION OF NARRATIVE TEXTS - Farahdiba Rahma Lutvita; Fauris Zuhri (Wiralodra English Journal, 2025)
The current study aimed to determine the extent to which eighth-grade junior high school students enhance reading comprehension by using Quizizz. This research intends to examine Quizizz's role in improving reading skills for narrative texts among junior high schools. The study used a quantitative research design with a quasi-experiment. It consisted of a control class and an experiment class. The research instruments were a pre-test and a post-test. The findings showed improved scores before and after treatment. Sig demonstrated a higher t-test result. The analysis used an independent t-test, involving fifty-five students. Data analysis showed statistically significant results, as the p-value was .000. The experimental group achieved an average score of 89.8. The control group achieved a score of 65.1. The effect size of the Quizizz score in reading comprehension was 0.6, indicating a large effect. It is possible to conclude that Quizizz is efficient in junior high school reading comprehension. Moreover, new areas and applications of Quizizz are available for future researchers allowing them to develop and implement studies that utilize various skills and variables.